1984
DOI: 10.3758/bf03205936
|View full text |Cite
|
Sign up to set email alerts
|

Flicker induces depth: Spatial and temporal factors in the perceptual segregation of flickering and nonflickering regions in depth

Abstract: If some regions of a random-dotfieldare flickered, then the nonflickering areas appear to stand out in depth in front of the flickering regions. This perception of depth is optimal within a limited range of temporal frequencies. The average temporal luminance of the flickering and nonflickering regions was kept equal, so the depth segregation is not due to a luminance difference. In fact, depth is seen even when the average temporal luminance of the flickering regions is twice that of the steadily presented re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
27
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 9 publications
2
27
0
Order By: Relevance
“…They found that for a range of spatial frequencies, from 8 to 0.5 cycles per degree (cpd), the region filled with the relatively lower spatial frequency sine-wave grating tends to be seen as the background behind the region filled with the higher spatial frequency grating, which in tum tends to be seen as the figure (see Figure 1). Wong and Weisstein (1984 found that regions of flickering dots tend to be seen as the background behind regions of stationary dots, which in tum are seen as the figure. The transient-sustained continuum of visual response sensitivity (e.g., see Giaschi, Anstis, & Rogers, 1988;Hess & Plant, 1985;Kelly, 1972Kelly, , 1979Koenderink & van Doorn, 1979;Robson, 1966;van Nes, Koenderink, & Bouman, 1967;Watson & Nachmias, 1977), where visual responses to higher spatial frequencies are generally associated with responses to lower temporal frequencies and…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…They found that for a range of spatial frequencies, from 8 to 0.5 cycles per degree (cpd), the region filled with the relatively lower spatial frequency sine-wave grating tends to be seen as the background behind the region filled with the higher spatial frequency grating, which in tum tends to be seen as the figure (see Figure 1). Wong and Weisstein (1984 found that regions of flickering dots tend to be seen as the background behind regions of stationary dots, which in tum are seen as the figure. The transient-sustained continuum of visual response sensitivity (e.g., see Giaschi, Anstis, & Rogers, 1988;Hess & Plant, 1985;Kelly, 1972Kelly, , 1979Koenderink & van Doorn, 1979;Robson, 1966;van Nes, Koenderink, & Bouman, 1967;Watson & Nachmias, 1977), where visual responses to higher spatial frequencies are generally associated with responses to lower temporal frequencies and…”
mentioning
confidence: 99%
“…As with the early investigations of visual sensitivity to spatial and temporal frequency (see Olzak &Thomas, 1986 andWatson, 1986 for reviews), the initial investigations of the visual system's responses to figure and ground considered only spatial or temporal frequency separately while holding the other physical dimension constant (Klymenko & Weisstein, 1986;Wong & Weisstein, 1984). Below, for suprathreshold stimuli, we systematically examine the combined influence of spatial and temporal frequency on figure-ground organization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The usual paradigm involves a visual field divided into two or more areas flickering at different rates. Typically, flickering areas are perceived as more distant than nonflickering areas, and areas with higher flicker rates are perceived as more distant than areas of slower flicker Klymenko, Weisstein, Topolski, & Hsieh, 1989;Wong & Weisstein, 1984a, 1984b, 1985, 1987. These effects are quite robust, remaining unaffected by variations in texture (e.g., Wong & Weisstein, 1985) or in the shapes of the flickering and nonflickering areas (e.g., Wong & Weisstein, 1984b, 1985, 1987, or by the presence or absence of contours surrounding the areas (Wong & Weisstein, 1987).…”
mentioning
confidence: 66%
“…
Previous research (e.g., Wong & Weisstein, 1984a, 1985 has shown that flickering stimuli appear to be more distant than nonflickering stimuli at the same physical distance. Given this relation between flicker and perceived depth, inappropriate constancy scaling theories predict that flickering stimuli should be perceived as larger than nonflickering ones.
…”
mentioning
confidence: 99%